An Improved Detection of Circulating Tumor DNA in Extracellular Vesicles-Depleted Plasma - Sun, Li; Du, Meijun; Kohli, Manish; Huang, Chiang-Ching; Chen, Xiaoxiang; Xu, Mu; Shen, Hongbing; Wang, Shukui; Wang, Liang (Frontiers in Oncology, 2021)
Circulating tumor DNA (ctDNA) in plasma has been used as a biomarker for cancer detection and outcome prediction. In this study, we collected the five precipitates (fractions 1–5) and leftover supernatant plasma component (fraction 6) by a sequential centrifugation in plasma samples from nine small cell lung cancer (SCLC) patients. The fractions 3, 5 and 6 were large vesicles, exosomes and extracellular vesicles (EVs)-depleted plasma, respectively. Fragment size analysis using DNAs from these fractions showed dramatical differences from a peak of 7–10 kb in fraction 1 to 140–160 bp in fraction 6. To determine ctDNA content, we performed whole genome sequencing and applied copy number-based algorithm to calculate ctDNA percentage. This analysis showed the highest ctDNA content in EV-depleted plasma (average = 27.22%), followed by exosomes (average = 22.09%) and large vesicles (average = 19.70%). Comparatively, whole plasma, which has been used in most ctDNA studies, showed an average of 23.84% ctDNA content in the same group of patients. To further demonstrate higher ctDNA content in fraction 6, we performed mutational analysis in the plasma samples from 22 non-small cell lung cancer (NSCLC) patients with known EGFR mutations. This analysis confirmed higher mutation detection rates in fraction 6 (14/22) than whole plasma (10/22). This study provides a new insight into potential application of using fractionated plasma for an improved ctDNA detection.